Order fulfilment process for a large online retail in Singapore. (2015) - Tan, Albert; Mitra, Sumit
Changes in customer shopping habits (e.g., using internet and mobile devices for shopping products and services) have created new channels for retailing and this development of new channels have made traditional retailers to relook at their operations and to offer their products and services through these new channels. The success of many online retailers such as Amazon.com has led to loss in market shares for traditional retailers. To cater to the changes in customer behaviour and to hedge against risk of losing market share to pure play online retailers, traditional retailers are looking at multi-channel retailing options, where customers can buy products and services through a wide range of channels depending on their needs. This paper examines different order fulfilment models that are used by many of the multi-channel retailers by considering the key resources, input and outputs required. And finally, it describes a costing model that can help to determine if the company need additional resources and the volume of orders required to break even.